Differential cellular composition of human palatine and pharyngeal tonsils. (December 2018) - Stanisce, Luke; Sims, Etty; Hou, Cheryl; Koshkareva, Yekaterina; Gaughan, John P.; Kuzin, Igor; Bottaro, Andrea
Highlights: Tonsils and adenoids from the same patient have different cellular composition. Tonsils harbor higher germinal center B cell numbers compared to adenoids. Plasmacytoid dendritic cells are more abundant in adenoids than in tonsils. Tonsils have higher fibroblastic reticular and lymphatic endothelial cell fractions. Abstract: Objective: The goal of this study was to gain a better understanding of the potential functional specialization of palatine and pharyngeal tonsils, by comparing their cellular composition in paired specimens from a large cohort of adenotonsillectomy patients. Design: Resident B cell, T cell, dendritic cell, and stromal cell subsets were characterized using multicolor flow cytometry in palatine and pharyngeal tonsil specimens from 27 patients, age 2–34 years. Results: Paired comparisons showed highly significant intra-individual differences in resident cell subsets of palatine and pharyngeal tonsils. Palatine tonsils harbored higher fractions of germinal center B cells/plasmablasts and IgD- CD27- double-negative B cells, and conversely lower fractions of IgD + CD38- resting naïve B cells compared to pharyngeal tonsils. Palatine tonsils also showed lower fractions of plasmacytoid dendritic cells, and higher percentages of two subsets of stromal cells - fibroblastic reticular cells and lymphatic endothelial cells - compared to pharyngeal tonsils from the same individual. Conclusions: Despite their physical proximity and histological similarities, palatine and pharyngeal tonsils display marked intra-individual differences in their cellular composition with regard to functionally important immune and stromal subsets. These differences are likely to have immunologic, pathologic, and physiologic significance.